ДИДАКТИЧНІ УМОВИ СТВОРЕННЯ ПРОБЛЕМНИХ СИТУАЦІЙ У ПРОЦЕСІ ВИВЧЕННЯ ІСТОРІЇ (Педагогіка вищої та середньої школи, 2007)
The problem situation is the obligatory component of scientific knowledge. The didactic conditions of création and effective functioning of the problem situations during studying History are opened in the article.